Game theory and coopetition - Ferreira, M. A. M.; Matos, M. (Journal of Economics and Engineering, 2014)
Through this paper it is intended to show how the game theory helps to understand the common space between the concurrence and the cooperation. This understanding is essential to formulate useful strategies when the result depends on a great number of interdependent factors. All this is illustrated with real life situations.